2009
DOI: 10.1016/j.jep.2009.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of Rheum officinale Baill. induces apoptosis in human lung adenocarcinoma A549 and human breast cancer MCF-7 cell lines

Abstract: This suggests that the water extract of Da Huang exerts potential anticancer activity through growth inhibition and apoptosis on MCF-7 and A549 cells lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 15 publications
0
42
0
2
Order By: Relevance
“…Emodin is also observed naturally in a number of widely used Chinese medicinal herbs, including Rheum officinale (8) and Polygonam cuspidatummedicine (9). It has been widely studied for its antibacterial, diuretic, immuno suppressive, anti-inflammatory and vaso relaxant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Emodin is also observed naturally in a number of widely used Chinese medicinal herbs, including Rheum officinale (8) and Polygonam cuspidatummedicine (9). It has been widely studied for its antibacterial, diuretic, immuno suppressive, anti-inflammatory and vaso relaxant effects.…”
Section: Introductionmentioning
confidence: 99%
“…The methanol extract of Scutellaria orientalis showed potent anti-leukemic activity against HL-60 cell line (Ozmen et al, 2010). The water extract of Rheum officinale exhibited significant antiproliferative activity by inducing apoptosis in MCF-7 and A549 cell lines (Li et al, 2009). A potent antiproliferative activity was also reported for the hexane extract of Casearia sylvestris stem bark against different cancer cell lines (Mesquita et al, 2009) and the butanol extract of Pfuffia paniculata demonstrated high cytotoxic activity against MCF-7 cell line (Nagamine et al, 2009).…”
Section: The Use Of Plants In Cancer Therapymentioning
confidence: 83%
“…Relevant antimitochondrial effects were demonstrated in some cases, eventually leading to cell apoptosis 7,8,10,11,33 . The colony formation assay was developed to detect the growth inhibitory effects of drugs on the anchorageindependent growth of colonies 18 . There are many studies about the antitumoral effects of Au(III) and Pt(II) compounds, but any of them were carried out for CFA assay.…”
Section: Discussionmentioning
confidence: 99%
“…The antineoplastic activities of [Au(phen)Cl 2 ]Cl and Pt(phen)Cl 2 were investigated through CFA assay as described in Li et al 18 with modifications in A549 cell line. Colony inhibition was calculated with the following formula: Colony forming inhibition % = 100 × (1-colony number of drug treated group/colony number of control group) 19 .…”
Section: Soft Agar Colony Forming Assaymentioning
confidence: 99%
See 1 more Smart Citation